An integrated surveillance in Zhejiang Province: ecological and pathogen survey of vectors and reservoir hosts in 2024 - Wang, Jinna; Luo, Mingyu; Liu, Qinmei; Li, Tianqi; Guan, Zhou; Gong, Zhenyu; Hou, Juan; Sun, Jimin; Jiang, Jianmin (Frontiers in Veterinary Science, 2026)
IntroductionIn this study, an integrated surveillance framework was employed to simultaneously quantify the population densities of key vectors and reservoir hosts and screen them for associated pathogens across Zhejiang Province, China.MethodsThe light trap method, larval pipette method, fly trap method, sticky trap method, trap-night method, tick-picking method, dragging method, visual inspection method, and chigger mite picking method were used for the ecological surveillance of mosquitoes, flies, cockroaches, rodents, ticks, bedbugs, and chigger mites. Rodent samples were screened for Dabie Bandavirus, Hantavirus, Leptospira interrogans, Rickettsia typhi, and Orientia tsutsugamushi. Mosquito samples were tested for dengue, yellow fever, Japanese encephalitis, West Nile, Zika, and chikungunya viruses. The descriptive statistics were used for analysis.ResultsIn 2024, the mosquito density in Zhejiang Province was 16.03 mosquitoes per trap-night, with Culex tritaeniorhynchus (59.05%) and Culex pipiens pallens (31.37%) being the dominant species. Livestock sheds harbored the greatest mosquito densities, averaging 81.07 mosquitoes per trap-night. The average BI was 12.97. The rodent density was 0.34 rodents per 100 trap-nights, and the dominant species was Rattus norvegicus. The fly density was 3.06 flies per trap, with Sarcophagidae species being dominant. The cockroach density was 0.44 cockroaches per trap, with Blattella germanica comprising 97.13% of the total catch. The tick densities were 0.51 ticks per animal and 0.35 ticks per flag per 100 m. No bedbugs were detected. The chigger mite infestation rate was 71.11%. Regarding rodent-borne pathogens, the positivity rates for Hantavirus, L. interrogans, and O. tsutsugamushi were 2.42, 10.46, and 0.16%, respectively. No Dabie Bandavirus or R. typhi were recorded. All 27,402 mosquitoes tested negative for the target pathogens.ConclusionThis integrated surveillance established baseline metrics for important vectors and reservoir hosts, furnishing evidence-based support for the ongoing management and prevention of vector-borne diseases.